Porphyry Body and Geological Structure Identification as Control of Low Sulphidation Epithermal System in Sangon, Kokap Sub-District, Kulonprogo Regency, Special Region of Yogyakarta, Indonesia - Akmal Dzulfikar; Anang Sahroni; Bachruddin Ashari; Diah Ayu R; Erwina Sofia Br Sembiring; Fadia Zharfa Ash S; Lilik Maryanto; Lutfi Afgani; M Nurrahman; M Rahmat C; Muslihul Zaim; Novita Triswi H; Riando Elang D; Siti Fadzillah; Ulya Habiburrahman (Jurnal Fisika Indonesia, 2020)
There is gravity measurement that is supported by magnetic measurement in Sangon to identify porphyry body and geological structure as low sulfidation epithermal system control. The survey area is 6.4 x 5.6 km for gravity method and 2.5 x 1.2 km for the magnetic method. The value of gravity anomaly after flat plane reduction processing is 122-142 mGal which is positive anomaly located in the north-eastern area and negative anomaly to 82- 102 mGal located in the south-western area. Whereas the magnetic residual anomaly is - 800-1300nT.Conducted 2.5 D modelling of gravity method that is based on local anomaly slice. The result of 2.5D modelling show that an intrusion body interpreted as Dacite intrusion as host rock which plays a role as a heat source of the mineralization system. The density of Dacite is 2.70 gr/cm3. The result of gravity modelling has a correlation with the result of magnetic modelling. Based on magnetic modelling, the intrusion body is located in the south-west.